PENDAMPINGAN MELALUI DIKLAT PENGENALAN DAN PENINGKATAN KEMAMPUAN BAHASA ASING BAGI SISWA DI DESA LEMBUNG KECAMATAN GALIS PAMEKASAN - Amalih, Ihwan; Bidari, Bidari (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
The importance of foreign language education for students is a necessary teaching and should be done.  Foreign languages must be taught to students given the impact of globalisation. Foreign language learning is done gradually and is taught only to the basics, not in depth. Learning methods vary, usually using songs, games, and things that children like with the aim that it is easy to memorise and remember. It is also important that parents play a role in the learning process using foreign languages so that students can add insight into knowledge and soft skills in the form of language. Therefore, the selection of a further excellent programme, namely mentoring through foreign language introduction and improvement training, is a perfect thing initiated by the Community Service Executive.